Global Trends in Teacher Management: Evidence from a Global Bibliometric Systematic Review (2020–2026) - Andi Nur Qalbi; Ardiansyah; Anshar (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study develops an integrative perspective on teacher management by addressing the fragmentation that characterizes much of the existing literature. Using a Systematic Literature Review (SLR) combined with bibliometric analysis, the study examines global research trends from 2020 to 2026. Data were retrieved from Scopus, Web of Science, and Google Scholar, resulting in 50 initial records, which were systematically filtered using the PRISMA protocol into 50 relevant articles. The findings reveal a substantial increase in scholarly attention to teacher management, particularly after the COVID-19 pandemic. More importantly, the focus of research has shifted from administrative concerns toward more complex dimensions, including teacher wellbeing, retention, and digital competence. Bibliometric mapping identifies four dominant clusters: professional development, teacher retention and motivation, digital transformation, and teacher wellbeing. Building on these insights, this study proposes an integrative model of teacher management that connects recruitment, distribution, professional development, and wellbeing within a systemic and adaptive framework. The analysis also highlights a divergence between developed and developing countries, emphasizing the importance of contextual adaptation. In the Indonesian context, this implies aligning global practices with local realities. This study contributes by bridging bibliometric evidence with comparative analysis, offering both theoretical integration and practical insights for sustainable education policy.